Draft Special Component Plan for Scheduled Castes 1980-85 and 1981-82 - Planning Commission (Planning Commission, 1981)
The Socio economic conditions of the scheduled castes who form about 8.3% of the total population of Kerala have to be Improved through more vigorous educational, economic and social measures. the steps taken so far could touch only a fringe of their problems and were too meagre to make any significant impact on their socio-economic conditions. In spite of the fact that the uplift of these people has been assigned a central position in the national Endeavour for development, the full dimensions, of their problems have not been appreciated so far with, the ""result that no clear strategy for their development has been evolved.
State Planning Board Government of Kerala